2021
DOI: 10.3389/fimmu.2021.729539
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele-Mediated Male Infertility: From the Perspective of Testicular Immunity and Inflammation

Abstract: BackgroundVaricocele (VC) is present in 35 - 40% of men with infertility. However, current surgical and antioxidant treatments are not completely effective. In addition to oxidative stress, it is likely that other factors such as testicular immune microenvironment disorder contribute to irreversible testicular. Evidence suggests that VC is associated with anti-sperm antibodies (ASAs), spermatogenesis and testosterone secretion abnormalities, and testicular cytokine production. Moreover, inhibition of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 108 publications
(145 reference statements)
1
35
0
9
Order By: Relevance
“…'regulation of immune effector process,' 'leukocyte apoptotic pro- Many studies have shown that inflammatory mechanisms play important roles in VC. 31,32 IL-1α and IL-1β have been reported to be increased in the VC model. 33,34 Camargo et al found that IL-1, IL-18 and caspase-1 decreased in semen after varicocelectomy by ELISAs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…'regulation of immune effector process,' 'leukocyte apoptotic pro- Many studies have shown that inflammatory mechanisms play important roles in VC. 31,32 IL-1α and IL-1β have been reported to be increased in the VC model. 33,34 Camargo et al found that IL-1, IL-18 and caspase-1 decreased in semen after varicocelectomy by ELISAs.…”
Section: Discussionmentioning
confidence: 93%
“…Many studies have shown that inflammatory mechanisms play important roles in VC 31,32 . IL‐1α and IL‐1β have been reported to be increased in the VC model 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…tMΦ produce several growth and differentiation factors for LC development ( Heinrich and DeFalco, 2020 ). In addition to testicular immunosuppression, tMΦ also locally regulate LC steroidogenesis ( Fang et al, 2021 ). Previous studies have delineated the phenotype of tMΦ in the normal testis, and tMΦ have been implicated in the development of azoospermia ( Hussein et al, 2005 ; Duan et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…These cells include macrophages, T cells, DCs, and mast cells associated with Leydig cells and Sertoli cells (SCs). Several studies have shown an overproduction of pro-inflammatory cytokines dependent on alterations of this microenvironment as in the case of varicocele [124]. The anti-inflammatory action of RSV could inhibit this cytokine hypersecretion, counteracting infertility.…”
Section: Resveratrol and Infertilitymentioning
confidence: 99%